2019
DOI: 10.1002/ejp.1504
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced pain modulation capacity among individuals with borderline personality disorder: A possible mechanism underlying their hypoalgesia

Abstract: Background Ample evidence suggests that individuals with borderline personality disorder (BPD) exhibit hyposensitivity to pain. Since the underlying mechanism of the pain hyposensitivity is unknown, we tested here for the first time whether this hyposensitivity is pain specific or exists also for innocuous sensation, and whether it is associated with enhanced descending pain modulation capabilities. Methods Participants were 55 women; 22 patients with BPD and 33 matched healthy controls. Testing included the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 67 publications
(123 reference statements)
1
10
0
Order By: Relevance
“…Admittedly, our cohort of adolescent patients, while describing hypoalgesia during self‐harming, did not show the increased pain thresholds observed in BPD adults; therefore, any conclusion may sound speculative. A recent study by Defrin and colleagues ( 2020 ) demonstrated an increased function of the endogenous pain modulation system in adult patients with BPD. The lack of differences between patients with BPD and patients with BPD and self‐injury behaviour led the authors to hypothesize that the enhanced pain modulation could be attributed to dissociation, a peculiar feature of BPD.…”
Section: Discussionmentioning
confidence: 99%
“…Admittedly, our cohort of adolescent patients, while describing hypoalgesia during self‐harming, did not show the increased pain thresholds observed in BPD adults; therefore, any conclusion may sound speculative. A recent study by Defrin and colleagues ( 2020 ) demonstrated an increased function of the endogenous pain modulation system in adult patients with BPD. The lack of differences between patients with BPD and patients with BPD and self‐injury behaviour led the authors to hypothesize that the enhanced pain modulation could be attributed to dissociation, a peculiar feature of BPD.…”
Section: Discussionmentioning
confidence: 99%
“…In another study by Defrin and colleagues [129], no significant correlation between elevated heat pain thresholds and a measure of trait dissociation (DES) was found in patients with acute BPD. On the other hand, higher trait dissociation (scores on the DES) predicted changes in the default mode network in response to painful heat stimulation in BPD patients with current self-injurious behavior [130].…”
Section: Dissociation and Pain Processingmentioning
confidence: 94%
“… 16 ], they found no evidence for altered proprioception, exteroception, and two-point discrimination [ 17 ] or warmth perception thresholds [ 9 , 10 ,c.f. 18 ], suggesting that somatosensory dysfunction is limited to affective stimuli. However, it remains unclearwhether altered somatosensory processing in BPD is specific for pain perception or also affects positive affective somatosensation.…”
Section: Introductionmentioning
confidence: 99%